Pengaruh Strategi Pembelajaran Relating, Experiencing, Applying, Cooperating, and Transferring (REACT) Terhadap Kemampuan Komunikasi Matematis Siswa Kelas VII di MTs Ash-Sohibiyah Bangun Purba - Lily Hardiyah Hafisani; Annajmi; Arcat (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2020)
ABSTRAK This study aims to determine whether or not there is an effect of the Relating, Experiencing, Applying, Cooperating, and Transferring (REACT) learning strategy on the mathematical communication skills of grade VII students at MTs Ash-Shohibiyah Bangun Purba. This type of research is a Quasi Experiment study with the Posttest Only Control Group Design design. This study's population were students of class VII MTs Ash-Shohibiyah Bangun Purba with a sample of class VII.1 and class VII.2. Samples were obtained using random sampling techniques. The experimental class uses the REACT strategy, while the control class uses conventional learning. This research instrument is a question of a description of mathematical communication skills. Posttest data on mathematical communication skills obtained were analyzed data to test the hypothesis. The normality test results showed that data were normally distributed, and the homogeneity test results showed that the data had variants that were not homogeneous. Hypothesis testing used the t 'test because the data were normally distributed and not homogeneous. The results of the calculation concluded that there was an effect of the learning strategy of Relating, Experiencing, Applying, Cooperating, and Transferring (REACT) on the mathematical communication skills of grade VII students at MTs Ash-Shohibiyah Bangun Purba.